1978
DOI: 10.1104/pp.62.3.443
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Measurement of Nitrogen Fixation Estimated by Acetylene-Ethylene Assay and Nitrate Absorption by Soybeans

Abstract: An apparatus was designed for simultaneous measurement of rates of N2 fixation estimated by C2H2-C2H4 assay (N21 C2H21 fixation) and N03-absorption by roots of intact, nodulated soybeans (Glycine max IL.I Merr.). The principal design features include: (a) a gas-tight mist chamber in which nodulated roots can be exposed simultaneously to C2H2 in the gas phase and to a lquid phase containing N03 sprayed in a fine mist; and (b) provision for sampling the gas phase for C2H4 determination, and the liquid phase for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 18 publications
3
33
0
Order By: Relevance
“…has been investigated by a number of workers (10,28,29). Earlier work has established that NO3-reduction in the leaves is chiefly responsible for N accumulation during vegetative development, reaching a maximum at beginning to full flower (12, 28).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…has been investigated by a number of workers (10,28,29). Earlier work has established that NO3-reduction in the leaves is chiefly responsible for N accumulation during vegetative development, reaching a maximum at beginning to full flower (12, 28).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier work has established that NO3-reduction in the leaves is chiefly responsible for N accumulation during vegetative development, reaching a maximum at beginning to full flower (12, 28). A sharp decline in leaf NR2 activity has been reported to follow within the 2 to 3 weeks after flowering (10,29 of N03-resulted in no increase in activity. Shaner and Boyer (24,25) reported that a variety of factors which decreased the movement of nitrate from roots to leaves resulted in a parallel decrease in NR activity in soybean.…”
mentioning
confidence: 98%
“…In addition, soybeans can also absorb and assimilate inorganic nitrogen, in the form of nitrates, from the soil [18]. The combined process of nitrogen fixation from atmospheric nitrogen and nitrogen assimilation from the soil ensure that soybean meet its large nitrogen demand for the production of protein rich seeds [18].…”
Section: Nhmentioning
confidence: 99%
“…The interaction of these processes can be studied only by more novel approaches than those allowed by conventional techniques. To facilitate the simultaneous measurement of NH4' absorption and N2 (acetylene) fixation of intact soybeans, a mist apparatus developed by Wych and Rains (23) was used in this study.…”
mentioning
confidence: 99%
“…Nodules were separated from the dried roots, counted, and weighed. Acetylene and ethylene were determined by gas chromatography (23 was 9 ,imol NH4', and, at flowering, was 10 ,umol NH4' for unnodulated and nodulated soybeans. Decreasing acidity produced no significant change in the acetylene reduction rate of flowering nodulated plants (Table III).…”
mentioning
confidence: 99%